Ichthyofauna from Santos-São Vincente upper estuary: a study before and during fire at Santos port terminal (Research, Society and Development, 2020)
Studies accounting the ichthyofauna composition of the Santos-São Vincente estuary-bay and Bertioga channel complex (SSEBBC) are scarce, even with its high ecological and economical importance. In this sense, the present study performed a checklist of the ichthyofauna from the SSEBBC aiming to report the distribution, diet, habitat, economic importance, and conservation status of the collected fish species. Twenty-four (24) monthly collecting campaigns were conducted between March 2013 and February 2015. In each survey, four locations around Bagres Island were sampled with the aid of gill nets with standardized effort. Dead fish specimens were also collected during the accidental fire that occurs on the Terminal Químico de Aratú S.A. (TEQUIMAR) between April 2nd and 10th of 2015. A total of 172 fish specimens were collected, where 50.6% were carnivorous; 35.5% were marine-estuarine; 44.2% with high occidental Atlantic Ocean distribution; 44.8% were a high important food resource. Regarding the conservation status, these fish species were classified as “low-worries” in 76.2% for the global evaluation; 95.3% in national evaluation; and 55.2% in São Paulo State evaluation. Moreover, 53 new fish species were catalogued for the Santos-São Vincente estuary-bay, where 12 were collected during the field monitoring and 41 during the fire monitoring. Fifty-eight (58) fish species collected during the field campaigns were categorized like “insufficient data”; 3 as alien species (Oreochromis niloticus, Opsanus beta e Butis koilomatodon); and there was a rare record of Megalops atlanticus in São Paulo State. Besides of the high anthropization, the studied area presented high fish species richness and should be monitored to ensure the fish species conservation status.